Neuromachinacs of human movement - Enoka, Roger M. 1949- (Human Kinetics, 2008)
Drawing on the disciplines of neurophysiology and physics, this new edition explores how the nervous system controls the actions of muscles to produce human motion in relation to biomechanical principles. This contemporary approach is different from the traditional approach, which focuses solely on mechanics and does t consider the role of the sensory system in the control of human movement.Throughout the text, the content is visually reinforced with more than 750 illustrations, many of which are new or upgraded from the previous edition and include specific illustrations of the neuromechanics involved in sport and rehabilitation movements.To encourage a comprehensive learning experience, this edition follows a logical progression where each part builds on the material from the previous section. It begins with an introduction to the biomechanical terms and concepts commonly used to describe movement, focusing on the relation between force and motion. This book provides a scientific basis for the study of human movement while continuing to expand current kwledge in the fields of biomechanics and neurophysiology. By integrating these fields in a unique framework, this text offers professionals and students both valuable clinical information and inspiration to deepen their study of human movement.